Perancangan Interior Bandara Iskandar Pangkalanbun Dengan Pendekatan Eco-Friendly - Yolenta Dwi Putri (Intra, 2017)
Era development and people’s need to move quickly from one place to another, make the necessary of transportation increase, one of them is plane. Airport as a place of plane stop, become a place that accommodate many visitor from domestic or overseas. Iskandar Airport Pangkalanbun is one of the development airport in Central Borneo, also as the first gate that visitor coming, must be show the cultural image that attract and giving the impression that in mind from interior design. Therefore, emphasize of Iskandar Airport, Pangkalanbun design is eco-friendly that combine with local content of Central Borneo, which is then adjusted with user need on universal design.       This goal is solved by the design method that done from collecting actual data in the field, data processing and concluding the design problems from the existing, that visualized through design drawings include layout, floor and ceiling plan, mechanical electrical, and other addition interior systems. With room perspective as concept visualization which is used to help in problem solving.                Achievement of the main purpose of this design is uses of ecofriendly materials, the implications of the carvings philosophy and Central Kalimantan typical building, as well as the universal design that doesn’t rule out the possibility of disability users can feel the same interior experience like other users.